Antroquinonol reduces IL-1β production in macrophages through enhancing the DNA methylation of Tlr4 - Bin, Peng; Fu, Zhengyang; Wang, Zixu; Hung, Ifen; Liu, Chunxue; Peng, Wenjin; Wang, Kaijun; Mo, Jiahao (Frontiers in Nutrition, 2025)
IntroductionMacrophages represent one of the most pivotal immune cells in the innate immune responses of weaned piglets. Emerging studies have revealed that numerous plant- or fungal-derived extracts significantly modulate macrophage functions. Antroquinonol (Antro), a characteristic triterpenoid compound isolated from Antrodia camphorata, has been extensively documented for its anti-inflammatory properties, but the precise mechanisms remain unclear.MethodsIn this study, we established a macrophage polarization model in vitro, and evaluated the impact of Antro on inflammatory cytokine production in M1 macrophages. The expression of inflammatory pathway components was then measured to identify the specific targets regulated by Antro, and genetic manipulation approaches were further applied to validate these targets.ResultsAntro enhances the enzymatic activities of DNA methyltransferases and facilitates DNA methylation-mediated suppression of Tlr4 expression, thereby inhibiting NF-κB signaling, ultimately attenuating IL-1β production in macrophages.ConclusionOur study elucidates a multi-pathway for the anti-inflammatory effects of Antro, significantly enriching the theoretical framework of natural product-mediated immunomodulation (particularly plant/fungal extracts). These findings provide critical scientific support for developing A. camphorata-derived fermentation products as novel feed additives to enhance immune function in swine production.